IMPLEMENTASI SE DIRJEN PEMBINAAN KELEMBAGAAN AGAMA ISLAM TENTANG POLIGAMI DALAM MASA IDDAH: Studi Kasus di Kantor Urusan Agama Kecamatan Lowokwaru dan Pengadilan Agama Malang - Dewi Roma Maghviroh (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
Abstract: This article aims to explain the implementation of Circular Number D.IV / Ed / 17/1979 about polygamy in the period of religious court in Malang City and Office of Religious Affairs Lowokwaru and explain the marriage law carried out by a husband who is still in the midst of his wife who was divorced under the Law in Indonesia. Research method in this article used empirical juridical or field research with qualitative approach. The source of the data used interview and documentation. While, processing data method through several stages: editing, classification, verification and analysis of data. The result of this research are the circular letter about polygamy in the Iddah Period couldn’t be apply in the case because it never got into Religious Courts Of Malang, then it turned has been completed in Religious Affairs Office. The circular letter in Religious Affairs Office Lowokwaru not applied in real, but was changed by another form like making statement part of Rp.6000 he wouldn’t come back to his first wife. The law of male in marriage according to Islam is valid if he fulfil the pillars and the terms of marriage, but according to the positive law in Indonesia will be cancelled by the law because its contrary to article 4 of the Marriage Law and strengthen to article 42 Compilation of Islamic Law.